Should Aid Reward Performance? : Evidence from a Field Experiment on Health and Education in Indonesia - Olken, Benjamin A.; Onishi, Junko; Wong, Susan (American Economic Association, 2015)
We report an experiment in 3,000 villages that tested whether incentives improve aid efficacy. Villages received block grants for maternal and child health and education that incorporated relative performance incentives. Subdistricts were randomized into incentives, an otherwise identical program without incentives, or control. Incentives initially improved preventative health indicators, particularly in underdeveloped areas, and spending efficiency increased. While school enrollments improved overall, incentives had no differential impact on education, and incentive health effects diminished over time. Reductions in neonatal mortality in nonincentivized areas did not persist with incentives. We find no systematic scoring manipulation nor funding reallocation toward richer areas.